Understanding Effective Teaching Practices in Chinese Classrooms : Evidence from a Pilot Study of Primary and Junior Secondary Schools in Guangdong, China - Coflan, Andrew; Ragatz, Andrew; Hasan, Amer; Pan, Yilin (World Bank, Washington, DC, 2018)
This study documents the results of a pilot study jointly undertaken by the World Bank and the Guangdong Department of Education to assess teaching practices in public primary and junior secondary schools using the Classroom Assessment Scoring System tool. The tool was used to conduct classroom observations on an illustrative sample of 36 teachers in three counties across Guangdong. The pilot tested whether such a tool could be used to measure the strengths and weaknesses of teaching practices in the Chinese context. It also informed how classroom observations can be more consistently applied in the province's Quality Assurance and Monitoring and Evaluation system. On average, teachers in this sample scored high on classroom organization, but lower on emotional support and instructional support. While there was substantial variation in performance across teachers, there was only modest variation by county, urban versus rural school location, teacher type, grade, and years of experience. Teachers who believed that students should be the focus of instruction (those who espouse student-centered learning) scored significantly higher across all domains than teachers who believed that teachers should be the focus of instruction (those who espouse teacher-centered learning). Together the results from this pilot provide insights into how teacher training can address the most critical gaps in teaching practices.